PENGARUH SUKU BUNGA PINJAMAN, UMUR PERUSAHAAN DAN AGUNAN TERHADAP KEPUTUSAN PERMINTAAN KREDIT (Studi Kasus Pada Usaha Mikro, Kecil dan Menengah di Solo Raya) - Triono, BRM Suryo; Penawan, Adi; Haryanto, Aris Tri (Universitas Slamet Riyadi, 2021)
Collateral has a significant effect on credit demand decisions in micro, small and medium businesses. The age of the company has a significant effect on credit demand decisions in micro, small and medium businesses. Loan interest rates have a significant effect on credit demand decisions in micro, small and medium businesses. The population in this study was all SMEs in Solo Raya, SMEs in Solo Raya was 23,254. The reason for choosing this population is Solo Raya with the number of businesses, which is 23,254 businesses or 28.23% of the total number of businesses in the city of Surakarta. The sample studied was 100 respondents, the sample method used in this study was the Simple Random Sampling (random) method, using the Slovin formula. The results showed that collateral has a positive and significant effect on credit demand decisions. The age of the company has a positive and significant effect on credit demand decisions. Loan interest rates have a positive and significant impact on loan demand decisions